PENGARUH FAKTOR INTERNAL DAN EKSTERNAL PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR - Azizah, Silfiana; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This researchis aimed to find out the influence of internal and external factors on the firm value. In thisresearch the internal factors are proxyby the financing decisions, firm size, managerial ownership, dividendpolicy and profitability. Meanwhile, the external factors are proxyby the exchange rates. The samples aremanufacturing companies which are listed in Indonesia Stock Exchange in 2010â2014 periods. The samplingtechnique in this research has been carried out by using purposive sampling and 56 companies have beenobtained as samples. This research has been conducted by using multiple linear regressions analysis techniqueand the assistance of SPSS (Stastistical Product and Service Solution) Program. The results of this researchindicates that variablesi.e. : firmsize, dividend policy and profitability have positive influence to the firm value.Meanwhile the variablesi.e.: financing decisions, managerial ownership and exchange ratesdo nothaveanyinfluence to the firm value.Keywords: Financing decision, firm size, managerial ownership, dividend policy, profitability, exchange ratesand firm value